PENGARUH LINGKUNGAN URBAN DAN TINGKAT KEBISINGAN TERHADAP KUALITAS TIDUR PENDUDUK KOTA MEDAN - ALEXANDER PARLINDUNGAN MARPAUNG (LP2MTBM MAKARIOZ, 2022)
In North Sumatra Province, especially Medan City, the noise level exceeds the predetermined limit, where the noise makes people in Medna City experience problems with sleep quality, such as difficulty sleeping, waking up at night which results in poor health conditions of the population, especially productive residents, so that later residents can easily get other diseases due to poor sleep quality, where this is influenced by vehicle noise factors, noise factors in industry, noise factors in residential environments, and noise factors in public areas, such as in public places that disturb community conditions and also lead to disruption of people's sleep quality. This study aims to investigate the influence of urban environment and noise level on the sleep quality of residents in Medan City. Rapid urban growth often leads to high levels of noise and other environmental disturbances, which can have a negative impact on human health, including sleep disturbances. This study used analytical descriptive method with cross sectional approach. The number of respondents amounted to 80 people in several urban environments in Medan City, where data collection techniques were carried out using documentation studies, interviews with questionnaires and also using observation. Data analysis techniques can be performed using the distribution of respondents, and Univariate analysis. From the results of the study, it was concluded that from several risk factors that are vulnerable to lack of sleep quality, the age of >60 years is an age that is vulnerable to the condition of lack of quality sleep in the community, while for urban conditions that exist are urban conditions where traffic and transportation are chaotic and not neatly arranged.